Postgraduate Students' Usage Patterns, Perceptions, and Attitudes Toward Artificial Intelligence Applications in Learning: A Case Study of the University of Zawia, Libya - Abdulnasir Alsayd; Mohieddin Masoud; Mahmoud Abdullah; Naima Alzletni; Asmahan Maati; Amani Barka; Najah Baroud (PT. Pusmedia Group Indonesia, 2025)
This study examines the integration and impact of Artificial Intelligence (AI) applications and tools within postgraduate programs at the University of Zawia, Libya. In the context of rapid technological advancements, higher education in Arabic-speaking regions is increasingly shaped by social, economic, and religious factors. While AI is transforming global educational practices through adaptive learning platforms, virtual tutors, and personalized experiences, its adoption in Libyan universities remains limited and underexplored particularly in relation to ethical considerations and student preparedness. Employing a mixed-methods approach, this research combines quantitative survey data from 150 postgraduate students with qualitative insights to examine levels of awareness, perceptions, challenges, and usage patterns of AI tools in academic contexts. The data were analyzed using basic statistics, mainly percentages, to identify trends that support the study’s objectives. By exploring how students utilize AI to enhance their academic performance, the study aims to offer practical recommendations to promote AI literacy, address ethical concerns, and align institutional policies with technological advancements. The findings contribute to the broader discourse on the role of AI in higher education, with a focus on sustainable integration and the preservation of academic integrity within Libya’s educational institutions.